Skill Session on Writing Patient Assessments for Pediatric Clerkship Students - Sofia Khera (Association of American Medical Colleges, 2020)
Introduction Formulating written patient assessments requires the student to synthesize subjective and objective information and use clinical reasoning to reach a diagnosis. Medical students lack this skill, and clinical experience is not enough to acquire it. This session provides a structured process for learning how to formulate a patient assessment. Methods Third-year medical students participated in a large-group interactive skill session at the beginning of their pediatrics clerkship. Instructors following a scripted model walked students through practice examples to ultimately formulate a complete written patient assessment. The session covered data synthesis, use of appropriate medical terminology, and differential diagnosis development. Students used an audience response system to practice these skills. Results Over 1 academic year, 250 medical students participated in six sessions, with an average of 40–50 attendees per session. Over 90% of students completed pre- and postsession written patient assessments. These assessments were evaluated using portions of the Pediatric History and Physical Exam Evaluation grading rubric. The session had a positive effect on patient assessment formulation skills, with a significant increase in scores after the session. Discussion The session improved students' skill in generating more complete written patient assessments. Almost all students found the session valuable regardless of prior clinical experience. Nearly 50% of students felt inadequately prepared to formulate a written patient assessment prior to the session, revealing a skills gap for learners and a curricular teaching gap. This skill session provided a structured method and active learning format for teaching this essential clinical skill.